Plum pudding murder - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2009)
Rumor has it that "Lunatic Larry" Jaeger is in the red--an idea that takes a sinister turn when Hannah discovers the man himself dead as a doornail in his own office. It seems quite a few people would have liked to fill Larry's stocking with coal and then bash him with it. With so many suspects to investigate and the twelve days of Christmas ticking away, Hannah's running out of time to nab a murderous Scrooge who doesn't want her to see the New Year.